Combined effect of high hydrostatic pressure and ultraviolet radiation on quality parameters of refrigerated vacuum-packed tilapia (Oreochromis niloticus) fillets - Monteiro, Maria Lúcia Guerra (Sci Rep, 2018)
This study investigated the effects of high hydrostatic pressure (HHP) and ultraviolet radiation (UV-C), individually and combined, on the physical, chemical and bacterial parameters of Nile tilapia (Oreochromis niloticus) fillets stored at 4 °C for 14 days. Tilapia fillets were divided into four groups: control (untreated samples), UV-C, HHP, and UV-C combined with HHP (UV-C+HHP); UV-C was applied at dose of 0.103 ± 0.002 J/cm(2), and HHP at a pressure of 220 MPa for 10 min at 25 °C. All samples were analyzed for total aerobic mesophilic count (TAMC), total aerobic psychrotrophic count (TAPC), Enterobacteriaceae count, pH, lipid oxidation, total volatile basic nitrogen (TVB-N), ammonia (NH(3)), and biogenic amines. Although UV-C accelerated (P ≤ 0.05) the formation of cadaverine, both UV-C and HHP, alone or together, retarded bacterial growth and delayed the increase (P ≤ 0.05) in pH, TVB-N, NH(3) and biogenic amines during refrigerated storage, extending the shelf life of refrigerated tilapia fillets at least 2.5 times considering the TAMC counts. Lipid oxidation was unaffected (P > 0.05) by UV-C radiation, and decreased (P ≤ 0.05) by HHP and UV-C+HHP. HHP alone or combined with UV-C showed higher potential benefits for tilapia fillets preservation considering the positive influence on cadaverine levels and lipid oxidation.